ANTHROPOMORPHISM IN THE TALE OF BAYAN BUDIMAN - SYAM, ESSY; ARIS, QORI ISLAMI; SARI, YESSI RATNA (LINGUISTICA, 2024)
This research analyzes the element of anthropomorphism in the classical Malay literary work entitled "The Tale of Bayan Budiman". Anthropomorphism is the attribution of human characteristics and behaviors to non-human entities, such as animals and natural phenomena. In this tale, the main character, a Bayan bird, is depicted as having the ability to speak, give advice, tell stories, and lead like a human. This research employs qualitative textual analysis methods to explore the representations of anthropomorphism in the narrative, dialogues, and descriptions of the text. The findings reveal that anthropomorphism is used to convey moral messages, stimulate the reader's imagination, and reflect the Malay worldview on the relationship between humans and nature. However, anthropomorphism can also obscure the essence and nature of different living beings, especially for child readers. This research contributes to the preservation of Malay literary heritage and provides a deeper understanding of the use of anthropomorphism in classical works